Pengelolaan Konflik Koperasi Ela Laya Dalam Kemitraan Dengan Perusahaan Sawit Besar (PBS) Di Kotawaringin Timur - Muhamad Yusuf; Heriansyah Heriansyah (Restorica: Jurnal Ilmiah Ilmu Administrasi Negara dan Ilmu Komunikasi, 2019)
The cooperative Ela Laya was established in 2003 in the village of Barunang Miri in Kemitraaan with one of the major palm oil companies in East Kotawartimur, but the existence of a new cooperative in the year 2010. For 7 (Seven) years Ela Laya's cooperative through the dynamics. Conflicts that occur between the two parties have hindered cooperative performance in carrying out its functions and responsibilities to the fullest. The purpose of this research is to describe the management of the conflicts Ela Laya partnership with the Big Palm Company in East Kotawartimur with a direct approach to conflict facing. The research method used is descriptive sampling and the data is analyzed inductively. The results showed that the conflict management conducted by cooperatives resulted in the results after years of facing conflict directly. In the negotiation of mediation funds, obtained a new agreement that benefits both parties and the surrounding community. Previously, various efforts were made by cooperative managers to reach the point through strategic conflict management. Among other efforts, intervening interventions include changing approaches to conflict and reducing prejudice, to retract the masses to support changes by performing hobbies and direct anti-violent actions. Also obtained information, there is a caretaker effort to prevent conflicts to heat up and not turn violent. Cooperative managers also strive to maintain their presence by requesting protection and observation about the development of a field conflict situation.